2014
DOI: 10.1007/s13313-014-0298-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a new member of the 16SrV group of phytoplasma associated with Bischofia polycarpa (Levl.) Airy Shaw witches’ -broom disease in China by a multiple gene-based analysis

Abstract: Bischofia polycarpa (Levl.) Airy Shaw witches'-broom disease is widespread in southern China. Infected trees show symptoms of severely proliferating shoots, reduced leaf size, yellowing and reddening of leaves, and internode shortening. We detected the phytoplasma in diseased tissues by 4′,6-diamidino-2-phenylindole-HCl fluorescence microscopy and polymerase chain reaction using the universal primers P1/ P7. We conducted sequence similarity analyses based on 16S rRNA and 23S rRNA genes, the spacer region betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The results showed that the established ddPCR method was reliable for quantitative detection of AYL phytoplasma, with relatively good effect. The tuf gene is a functional protein coding gene and a relatively conserved sequence in the phytoplasma which plays an important role in protein translation and evolution of phytoplasma (Koui et al, 2003; Lai et al, 2014; Lee et al, 2000; Schneider et al, 1997; Yu et al, 2016,b, 2017, 2018). In the study, the tuf gene was used as a diagnostic assay for AYL phytoplasma for the first time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the established ddPCR method was reliable for quantitative detection of AYL phytoplasma, with relatively good effect. The tuf gene is a functional protein coding gene and a relatively conserved sequence in the phytoplasma which plays an important role in protein translation and evolution of phytoplasma (Koui et al, 2003; Lai et al, 2014; Lee et al, 2000; Schneider et al, 1997; Yu et al, 2016,b, 2017, 2018). In the study, the tuf gene was used as a diagnostic assay for AYL phytoplasma for the first time.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the established ddPCR method was reliable for quantitative detection of AYL phytoplasma, with relatively good effect. The tuf gene is a functional protein coding gene and a relatively conserved sequence in the phytoplasma which plays an important role in protein translation and evolution of phytoplasma (Koui et al, 2003;Lai et al, 2014;Lee et al, 2000; F I G U R E 3 Absolute quantitation of the ddPCR detection system for AYL phytoplasma using primers Atf/Atr and probe AtProbe. AYL1, AYL2 and AYL3 represent AYL samples; H1, H2 and H3 represent asymptomatic samples; ck1 represented TE buffer used for DNA extraction; ck2 represented ddH2O used for ddPCR reaction system.…”
Section: Detection Of Ayl Phytoplasma Targeting the Tuf Gene By Ddpcrmentioning
confidence: 99%
“…ALY is associated with the ALY phytoplasma, a member of the elm yellows (EY) phytoplasma group or 16SrV group, subgroup 16SrV-C [ 18 ]. Other members of this group are phytoplasmas causing diseases of trees and shrubs such as EY, flavescence dorée (FD) of grapevine, Palatinate grapevine yellows (PGY), spartium witches’-broom (SpaWB), rubus stunt (RuS), blackberry witches’-broom, cherry lethal yellows, flowering cherry decline, sweet cherry virescence, peach yellows in India, jujube witches’-broom, balanites witches’-broom, Japanese raisin witches’-broom, Bischofia polycarpa witches’-broom and Styphnolobium japonicum (previously known as Sophora japonica ) witches’-broom, and phytoplasmas infecting Clematis vitalba in Europe and hemp dogbane ( Apocynum cannabinum ) in New York state, respectively [ 2 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Similarly to other members of the EY group, ALY phytoplasma is a homogeneous pathogen at rDNA sequence level.…”
Section: Introductionmentioning
confidence: 99%
“…The elm yellows phytoplasma group, 16SrV, is divided into eight subgroups, 16SrV‐A to 16SrV‐I (Fránová et al, 2016) of phytoplasmas associated with serious diseases such as grapevine flavescence dorée (Martini et al, 1999), alder yellows (Lederer & Seemüller, 2007), elm yellows (Lee et al, 2004), rubus stunt (Malembic‐Maher et al, 2011), spartium witches’ broom (Marcone et al, 2004), cherry lethal yellows (Zhu et al, 1998), jujube witches’ broom (Jung et al, 2003), Balanites witches’ broom (Win et al, 2013), (Lai et al, 2014) and 16SrV‐I blackberry witches’ broom (Fránová et al, 2016). The reference strain of the elm yellows group is EY1 T classified to the 16SrV‐A subgroup (Lee et al, 1993).…”
Section: Introductionmentioning
confidence: 99%